2007
DOI: 10.1210/jc.2007-0359
|View full text |Cite
|
Sign up to set email alerts
|

The Uridine Diphosphate Glucuronosyltransferase 2B15 D85Y and 2B17 Deletion Polymorphisms Predict the Glucuronidation Pattern of Androgens and Fat Mass in Men

Abstract: The UGT2B15 D85Y and the UGT2B17 deletion polymorphisms are both predictors of the glucuronidation pattern of androgens/androgen metabolites. Our findings indicate that UGT2B17 is involved in 17-glucuronidation of mainly T but also of DHT and androstanediol and that UGT2B15 is involved in the 17-glucuronidation of androstanediol. Furthermore, these two polymorphisms are predictors of fat mass in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 15 publications
3
46
1
1
Order By: Relevance
“…We have reported previously from the EMAS cohort associations of the AR exon 1 CAG repeat polymorphism with endocrine and metabolic parameters (23), and of AR exon 1 CAG repeat and other polymorphisms with heel ultrasound parameters (8). Other genes with polymorphisms associated with androgen and/or estrogen levels in men include SHBG (28), CYP17 (29), CYP19A1 (30), 17␤HSD5 (31), and uridine diphosphate glucuronyltransferase 2B7 (UGT2B7) (32), but many potentially important polymorphic influences have apparently not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported previously from the EMAS cohort associations of the AR exon 1 CAG repeat polymorphism with endocrine and metabolic parameters (23), and of AR exon 1 CAG repeat and other polymorphisms with heel ultrasound parameters (8). Other genes with polymorphisms associated with androgen and/or estrogen levels in men include SHBG (28), CYP17 (29), CYP19A1 (30), 17␤HSD5 (31), and uridine diphosphate glucuronyltransferase 2B7 (UGT2B7) (32), but many potentially important polymorphic influences have apparently not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the relationship of the UGT2B genes and hormones showed that both the UGT2B15 D85Y polymorphism and the UGT2B17 CNV were associated with serum levels of AAG ( p < 0.001), but not with levels of another steroid glucuronide, 3a-diol-3-glucuronide, in a populationbased cohort of young adult (n = 1068; mean age = 18.9 years) and elderly (n = 1001; mean age = 75.3 years) Swedish men (Swanson et al, 2007). We did not determine 3a-diol-3-glucuronide levels in our study as AAG represents 80% of the combined isoforms of 3a-diol, and thus we felt measuring AAG, which gave a good overall measure of glucorinidation activity.…”
Section: Ugt2b Variants: Aag Levels and Prostate Cancer Riskmentioning
confidence: 98%
“…In addition, a polymorphism in the regulatory region of the UGT2B17 gene has been associated with altered levels of AAG (Hu et al, 2010). While both the UGT2B17 and UGT2B15 polymorphisms are significantly associated with AAG levels in European populations, no observations have been made in individuals of African descent (Hsing, 2001;Swanson et al, 2007;Olsson et al, 2011).…”
mentioning
confidence: 99%
“…First described by Murata et al (2003), this deletion, in the homozygous state, leads to substantially reduced levels of urinary testosterone glucuronide (Jakobsson et al, 2006;Juul et al, 2009) and, to a lesser extent, serum androstane-3␣,17␤-diol-17-glucuronide (Swanson et al, 2007). The deletion seems to be a predictor of fat mass and insulin sensitivity in men (Swanson et al, 2007) and is associated with susceptibility for osteoporosis (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%